Local Government Capability in Internal Control Implementation for Good Governance: Evidence from Palembang City - Jamiah Haryanti; Alfitri Alfitri; Slamet Widodo; Abdul Nadjib Abdul Nadjib (Universitas Medan Area, 2026)
This study examines the implementation of the Government Internal Control System (Sistem Pengendalian Intern Pemerintah/SPIP) in the Palembang City Government and analyses how local government capability shapes its contribution to good governance. Using a qualitative approach with a grounded theory design, data were collected through interviews and document review involving the Inspectorate, regional apparatus organisations, and relevant oversight actors. Data were analysed using the interactive model of Miles, Huberman, and Saldaña. The findings show three main points. First, SPIP has been formally institutionalised and is procedurally active, particularly within the Inspectorate through validation, quality assurance, and monitoring routines. Second, implementation remains uneven across regional agencies and is often treated as an administrative requirement rather than an embedded managerial practice. Third, leadership commitment, supervisory capacity, human resource capability, inter-unit coordination, and organisational learning are the main factors influencing implementation quality. The study concludes that government capability plays a central role in linking formal internal control design to good governance outcomes. These findings suggest that strengthening SPIP requires adaptive institutional capability across government units.